A conceptual approach to density‐dependent management of zoo animals kept in herds. Issue 1 (12th March 2013) - Müller, D. W. H.; Hammer, S.; Hammer, C.; Hatt, J.‐M.; Clauss, M.
Abstract : Successful management of herds of captive wildlife (small populations) requires monitoring of herd size over years. In many zoos, herd size is documented in the course of annual inventories without considering other epidemiological parameters. Here, the concept of the 'anti‐clockwise cycle' of the relation between mortality and population size is introduced for herd management. Four different phases of this cycle can be distinguished: (I) herd size increases while mortality decreases; (II) herd size and mortality increase; (III) herd size decreases and mortality still increases; (IV) herd size and mortality decrease. Consequently, a herd can still prosper in size (I, II) while an increase in mortality rates (II) already indicates that it is heading towards collapse (III). All four phases of the cycle of herd development could be observed in 28 small, closed ruminant breeding groups at the Al Wabra Wildlife Preservation, Qatar. Applications of the concept presented here to evaluate herd development in captivity may help to stabilize or even increase the size of a herd in care, which is particularly important for breeding herds of threatened species. The 'anti‐clockwise cycle' shows that a simple monitoring of the herd size in numbers is not enough to evaluate the sustainability and quality of the herd.